Hysteretic Dynamics of Flashback in a Low-Swirl Stabilized Combustor. Issue 2 (1st February 2017) - Szasz, R.; Subash, A. A.; Lantz, A.; Collin, R.; Fuchs, L.; Gutmark, E.
ABSTRACT: The hysteretic behavior of flashback (FB) and flash forward (FF) in methane and natural gas flames, stabilized by a low swirl fuel injector, is investigated using high speed OH* chemiluminescence and particle image velocimetry. Due to the lack of vortex breakdown, the two mechanisms discussed are boundary layer and turbulence induced FB. Two hysteresis cycles were identified, one when FB is induced by increasing the equivalence ratio starting from lean conditions, and the other by decreasing the equivalence ratio starting from rich conditions. Impact of relevant parameters including Reynolds number (Re), equivalence ratio, fuel type, combustion chamber geometry, preheating, and mixing tube protrusions are investigated. As Re is increased, the equivalence ratio at which both rich and lean flashbacks occur approaches stoichiometric conditions. However, the range of the hysteresis cycle between FB and FF is independent on Re. The transition processes during FB and FF are quite variable and their duration is independent on Re. The mean duration of FB transition initiated from lean conditions is nearly twice longer than the rich branch and also longer than both the lean and rich FF. The geometry of the combustion chamber affected neither FB nor FF. However, preheating increased the equivalence ratio at which FB occurred but did not affect FF. Also, FB had significant effect on the mean flow field.